Aqueous Oxidation of Sulfonamide Antibiotics: Aromatic Nucleophilic Substitution of an Aniline Radical Cation. Issue 34 (4th July 2013) - Tentscher, Peter R.; Eustis, Soren N.; McNeill, Kristopher; Arey, J. Samuel
Abstract Sulfonamide antibiotics are an important class of organic micropollutants in the aquatic environment. For several, sulfur dioxide extrusion products have been previously reported upon photochemical or dark oxidation. Using quantum chemical modeling calculations and transient absorption spectroscopy, it is shown that single‐electron oxidation from sulfadiazine produces the corresponding aniline radical cation. Density functional theory calculations indicate that this intermediate can exist in four protonation states. One species exhibits a low barrier for an intramolecular nucleophilic attack at the para position of the oxidized aniline ring, in which a pyrimidine nitrogen acts as a nucleophile. This attack can lead to a rearranged structure, which exhibits the same connectivity as the SO2‐extruded oxidation product that was previously observed in the aquatic environment and characterized by NMR spectroscopy. We report a detailed reaction mechanism for this intramolecular aromatic nucleophilic substitution, and we discuss the possibility of this reaction pathway for other sulfonamide drugs.